2018
DOI: 10.1557/adv.2018.57
|View full text |Cite
|
Sign up to set email alerts
|

Design, Manufacture, and In vivo Testing of a Tissue Scaffold for Permanent Female Sterilization by Tubal Occlusion

Abstract: Current FDA-approved permanent female sterilization procedures are invasive and/or require the implantation of non-biodegradable materials. These techniques pose risks and complications, such as device migration, fracture, and tubal perforation. We propose a safe, non-invasive biodegradable tissue scaffold to effectively occlude the Fallopian tubes within 30 days of implantation. Specifically, the Fallopian tubes are mechanically de-epithelialized, and a tissue scaffold is placed into each tube. It is anticipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Porous hydroxyapatite scaffolds which possess micropores (1–10 µm) and macropores (90–110 µm) by changing the solvent compositions (water–glycerol for micropores and water–dioxane for macropores) have been reported . More recently, collagen was freeze cast to create scaffolds for permanent female sterilization that was tested on successfully with rats . The effect of processing conditions was further tested and showed that lower freezing rate produced larger pores and thicker lamellar walls, resulting in decreased modulus but higher yield strength .…”
Section: Bioinspired Designs At Different Length‐scalesmentioning
confidence: 99%
“…Porous hydroxyapatite scaffolds which possess micropores (1–10 µm) and macropores (90–110 µm) by changing the solvent compositions (water–glycerol for micropores and water–dioxane for macropores) have been reported . More recently, collagen was freeze cast to create scaffolds for permanent female sterilization that was tested on successfully with rats . The effect of processing conditions was further tested and showed that lower freezing rate produced larger pores and thicker lamellar walls, resulting in decreased modulus but higher yield strength .…”
Section: Bioinspired Designs At Different Length‐scalesmentioning
confidence: 99%
“…We anticipate this mechanism of stabilization and biopolymer conformity in tubular structures [81] to translate to the ureter thereby eliminating the need for the double-J design in current clinical devices.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…In this study, we focus on confocal microscopy (CM) as a means of biopolymer scaffold characterization in the fully hydrated state to illustrate a new CM-based method for the semi-automated rigorous quantification of pore architecture and morphology. Highlighted is, how the new technique complements strengths of scanning electron microscopy (SEM) such as a high resolution and depth of field (Deville, 2017;Ratner et al, 2004) and how it helps overcome its weaknesses such as the typical limitation to the imaging of dry samples (Bozkurt et al, 2007;Divakar et al, 2018Divakar et al, , 2017Francis et al, 2017Francis et al, , 2013Lien et al, 2009;Loh and Choong, 2013;Re et al, 2015;Scotti and Dunand, 2018;Yin et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%